2019
DOI: 10.29244/jam.7.1.19-31
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Memengaruhi Persepsi Wakif terhadap Wakaf Uang di Kota Bogor

Abstract: Waqf has a potential in developing a social and economic aspect of society. The development of waqf instrument in the attempt of social and economic growth is able to be obtained through the new concept of waqf, that is cash waqf. However, the realization of cash waqf collection was not met its potential. Based on the previous studies, one of the factors that caused the low quantity of cash waqf collection was the people that had less awareness and comprehension towards cash waqf. Even several people that alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
1
6
0
3
Order By: Relevance
“…The attitude of waqf after having faith in money waqf will further encourage his intention and decision to carry out cash waqf with self-excellence for the sake of social welfare and the interests of the ummahunder Islamic law. The attitude-behavior towards waqf in money waqf is formed from his understanding of cash waqf, when the higher the perception of waqf towards money waqf, the higher the attitude he shows in money waqf (Fauziah & El Ayyubi, 2019). This study found that the attitude of waqif in Indonesia towards their behavior in making decisions with money is categorized as good.…”
Section: Effect Of Behavioral Beliefs (Attitudes) On Money Waqf Decismentioning
confidence: 78%
“…The attitude of waqf after having faith in money waqf will further encourage his intention and decision to carry out cash waqf with self-excellence for the sake of social welfare and the interests of the ummahunder Islamic law. The attitude-behavior towards waqf in money waqf is formed from his understanding of cash waqf, when the higher the perception of waqf towards money waqf, the higher the attitude he shows in money waqf (Fauziah & El Ayyubi, 2019). This study found that the attitude of waqif in Indonesia towards their behavior in making decisions with money is categorized as good.…”
Section: Effect Of Behavioral Beliefs (Attitudes) On Money Waqf Decismentioning
confidence: 78%
“…According to (Amalia & Puspita, 2018), religious understanding plays 54% role in determining interests of Jakarta's resident in cash waqf contribution. Furthermore (Fauziah & El Ayyubi, 2019) (Jazil et al, 2019) (Ekawaty & Muda, 2015) stated that the low level of waqf literacy affects intention to participate in waqf. Nevertheless, there have been no studies linking Perceived Waqf as a factor affecting the intention of using digital waqf innovation.…”
Section: Perceived Waqf As Moderating Variable (Pw)mentioning
confidence: 99%
“…Conventional cash waqf fund rising faces various challenges on its development. Some of these challenges are: transparency and accountability of waqf institutions (Rusydiana & Rahayu, 2019); low public literacy towards waqf (Fauziah & El Ayyubi, 2019) (Ekawaty & Muda, 2015) (Jazil et al, 2019) which are influenced by education (Nizar, 2014); social cultural factors and lack of promotion (Adeyemi, Ismail, & Sabariah, 2016); issues related to waqf institutions and their legal instruments (Hasim, Lubis, & Ali, 2016); religious factors (Jazil et al, 2019) (Rizal & Amin, 2017) (Dennis et al, 2018) (Osman et al, 2014), trust in waqf management institutions, and convenient in performing endowments/ supported facilities (Jazil et al, 2019) (Shukor et al, 2017); uncertified and less qualified Nazir (waqf manager) as many Nazir treat their profession as side job (Huda, Rini, Mardoni, Hudori, & Anggraini, 2017) (Rusydiana & Rahayu, 2019); and the lack of creative and innovative marketing strategies (Rusydiana & Rahayu, 2019).…”
Section: Determinant Of Conventional (Offline) Waqf Fund Risingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedasarkan penelitian yang dilakukan oleh Fauziah (2018), sebanyak 72 persen dari total respondennya menerima konsep wakaf uang dan berpotensi untuk melakukan wakaf melalui uang. Berwakaf secara online merupakan fasilitas untuk wakif dalam berwakaf uang.…”
Section: Pendahuluanunclassified